A review of success factors in the promotion of prosocial behaviours as a preventive strategy in Juvenile Justice context in Spain - Barroso-Hurtado, Domingo; Bembibre Serrano, Judit (Revista Complutense de Educación, 2018)
The acquisition and strengthening of prosocial behaviors are associated with a reduction in the frequency of antisocial, aggressive or risk behaviors. Thus, its promotion in the context of the implementation of the Organic Law 5/2000, of 12 January, regulating the criminal responsibility of minors would be an effective strategy for the purposes of reeducation and social reintegration that it presupposes. Then, it will be necessary to review the possibilities that the law provides for their development, as well as to detect success factors that contribute to increasing the impact of such interventions. To that end, it will be carried out a comparative analysis of interventions aimed at the promotion of prosocial behaviors in the school context, in the programs developed in detention centers in Andalusia and, lastly, in the implementation of judicial measures of community service, tasks to educate for life in society and probation. The main findings show that an integral approach that involves working with the personal dimensions of temperament and cognitive, moral and socioafective development; the use of active methodologies; the training of the professionals who execute the program; or the involvement of families are among those success factors associated with the different interventions analyzed. Moreover, among the measures included in the Organic Law 5/2000, the community service as a judicial measure and as an out-of-court dispute settlement procedure (in both forms), as well as the conciliation and redress within the latter, result important in relation to the promotion of prosocial behaviors.